Biologic therapy: a boon for hidradenitis suppurativa‐like lesions complicating naevus comedonicus in a prepubertal child. (1st April 2019) - Sahu, P.; Aggarwal, P.; Dayal, S.; Kumar Jain, V.
Abstract: Click here for the corresponding questions to this CME article.